IDENTIFICATION OF NOVEL CYTOTOXIC PROSTAGLANDIN METABOLITES PRODUCED IN ARACHIDONOYL ETHANOLAMIDE-TREATED TUMOREGENIC KERATINOCYTES - Thati, Drisheka (East Carolina University, 2012)
Arachidonoyl ethanolamide (AEA) induces apoptosis in mouse tumorigenic keratinocytes (JWF-2 cells). Our previous data show that AEA is metabolized by COX-2 to pro-apoptotic J-series prostaglandins. COX-2 is an enzyme that is abundant in tumor cells but not in the normal epithelial cells surrounding the tumor. Thus, the pro-apoptotic J-series prostaglandins should be selectively synthesized in AEA-exposed tumor cells with elevated COX-2 expression. As such, AEA could be developed as a topical agent to treat non-melanoma skin cancer. The main goal of this project is to identify the specific J-series prostaglandins that are produced as a result of the metabolism of AEA by COX-2 using mass spectrometry. (ELISA analysis can detect J-series family prostaglandins but cannot distinguish between the individual J-series isoforms). Exogenous J-series prostaglandins were added to fresh cell culture medium, and the prostaglandins were extracted using solid phase extraction. Concentrated samples were then subjected to Liquid Chromatography/Electrospray Ionization /Mass Spectrometry (LC-ESI-MS) in negative mode for identification of J-series prostaglandin isoforms. Our data show good recovery of extracted species and acceptable resolution of these chemically similar standards. The AEA-treated cell culture medium and its control were extracted using the validated extraction protocol and analyzed using the method developed with LC-ESI-MS. The mass spectrum of AEA-treated, extracted and concentrated cell culture media clearly shows peaks at m/z ratio identified as the parent ion peak (M-H)⁻ of ethanolamide conjugates of the J-series prostaglandins. The identification of the ethanolamide conjugates was confirmed by performing tandem mass spectrometry. It was also observed that with increased AEA concentration, the mass spectral intensity of the ethanolamide conjugates of J-series prostaglandins increased. The effect of COX-2 inhibitor and N-acetyl cysteine on the production of ethanolamide conjugates of J-series was also studied. The identification of the cytotoxic ethanolamide conjugates of J-series prostaglandins as the metabolites of AEA synthesized in tumor cells help us to determine the mechanism by which AEA induces apoptosis.
Keywords: Chemistry; Pharmacology; Prostaglandins; Skin--Cancer--Research; Apoptosis; Keratinocytes